Soil arthropos study in two differents ecosystems from cauca river - colombia (2005)
Two different ecosystems: a native forest and a pine plantation were chosen on the west side of Cauca river to study the arthropod composition in the upper horizons and interior ones. Catches were made through pitfall traps and Berlesse techniques and population comparisons were made in all horizons based on Diversity, Frequency, Abundance and Biomass indexes. Results show differences in arthropods fauna composition and its abundance in both ecosystems  with all indexes used, and differences in biomass and functional groups measurements, could indicate changes in ecosystem composition and relationships due to man perturbations.